Capturing the Experiences of International Teaching Assistants in the US American Classroom. (June 2014) - Hebbani, Aparna; Hendrix, Katherine Grace
Abstract : This chapter presents findings from a qualitative study which investigated the perceptions of twenty‐five ITAs toward US American undergraduates. The participant cohort comprised fourteen PhD and eleven master's students, of which, three were male and twenty‐two were female ITAs teaching oral communication or a communication course requiring at least two graded assignments. The responses gathered via an online survey were content analyzed using Leximancer, a text analytic software program. We found that the master's students reflected more about issues pertaining to their own public speaking and confidence, while the PhD students were more concerned with the preparation and presentation of the course material. In addition to discussing these findings, one coauthor of this study adds her reflexive voice to the experience of being a nonnative English speaker teaching American students.